(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2025)
The instances of wild bird intrusion in the standing crops cause significant losses to agricultural yields which needs for a creative and effective solutions. This study investigates a method to apply smart farming technology to this problem; for sustainable management of the issue by introducing Internet of Things (IoT) devices and automated deterrent systems, for small and medium farms, to develop a proactive and strong farm protection system. By combining these technologies, a more secure and sustainable farming environment may be created through real-time monitoring, early bird detection, and prompt response mechanisms. This is evidence of the IoTs’ potential to revolutionize conventional farming methods, improve bird-human cooperation, and protect farmers’ agricultural investments. The study explores potential ways to control birds’ incursions into farmers’ standing crop fields, particularly in Nepalese cereal-based farming systems. An approach to the issue would be to repel the approaching birds in farmland by using LED technology. The creative application of LED (Light Emitting Diode) technology serves as an inexpensive, practical method of keeping encroaching birds out of agricultural fields without endangering the animals or the farm. The results present an innovative way to deal with the difficulties posed by a variety of instances of animal-bird intrusion in agricultural lands, which contributes to the rapidly developing matter of wildlife and wild bird management. This approach can be a base for providing farmers with a practical, ethically acceptable, and ecologically sound way to reduce confrontations between humans and nature while preserving crops and birds that encourage sustainable coexistence.